Women's land rights in the transition to individualized ownership: implications for tree resource management in Western Ghana - Quisumbing, Agnes R.; Payongayong, Ellen; Aidoo, J. B.; Otsuka, Keijiro (International Food Policy Research Institute, 1998)
Based on a survey of 60 villages in Western Ghana, where cocoa is the dominant crop, this study explores evolutionary changes in land tenure institutions on women's land rights and the efficiency of tree resource management....With increasing population pressure, customary land tenure institutions in Western Ghana have evolved toward individualized systems in order to provide appropriate incentives to invest in tree planting and management. Contrary to the conventional wisdom, individualization of land rights has strengthened women’s rights to land. If labor-intensive agriculture increases the demand for female labor, as in the case of cocoa in Ghana, a woman's labor on her husband's plot may represent a form of sweat equity that confers individualized land rights to her."